Daya Terima dan Kandungan Gizi Sosis Ikan Nila dengan Penambahan Tepung Kacang Hijau dan Brokoli - Maya Akmilia Rachmanonny; Rita Ismawati (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Fish sausage is a processed food with raw materials of at least 50% surimi mixed with flour and other ingredients then filled into a sleeve, and then boiled or steamed. This research aims to determine the effect of the addition of mung bean flour and broccoli on the acceptability and nutritional content in fish sausage products tilapia sausage products as anemia-preventing snacks for teenage girls. girls. This research is an experimental research with 3 treatments of adding mung bean flour and broccoli at each 10%:10%, 13%:7%, 16%:4%. Organoleptic test was conducted on 35 untrained panelists using a hedonic scale. Organoleptic test data were analyzed statistically using the Kruskal Wallis non-parametric test and followed by the Mann Whitney test if found with Mann Whitney test if there was a difference. Determination of the best formula was taken from the highest average and calculation of the De Garmo method. The results showed that the addition of the addition of mung bean flour and broccoli influenced the level of but did not affect the color, aroma, shape, and texture of tilapia sausage, and texture of tilapia sausage. The best sausage product based on acceptability acceptance is the second formula. Nutritional content test results of the best formula per 100 grams were 175.7 kcal of energy, protein 10.26%, iron 079 mg, folic acid 429.00 mcg, and vitamin C 3.925 mg. Future research is expected to examine shelf life of tilapia sausage.